BMI Is Associated With Increased Plasma and Urine Appearance of Glucosinolate Metabolites After Consumption of Cooked Broccoli - Charron, Craig S.; Vinyard, Bryan T.; Jeffery, Elizabeth H.; Ross, Sharon A.; Seifried, Harold E.; Novotny, Janet A. (Frontiers in Nutrition, 2020)
Introduction: Preclinical studies suggest that brassica vegetable diets decrease cancer risk, but epidemiological studies show varied effects, resulting in uncertainty about any health impact of brassicas. Factors controlling absorption of glucosinolate metabolites may relate to inconsistent results. We reported previously that subjects with BMI > 26 kg/m2 (HiBMI), given cooked broccoli plus raw daikon radish (as a source of plant myrosinase) daily for 17 days, had lower glucosinolate metabolite absorption than subjects given a single broccoli meal. This difference was not seen in subjects with BMI < 26 kg/m2 (LoBMI). Our objective in this current study was to determine whether a similar response occurred when cooked broccoli was consumed without a source of plant myrosinase. Methods: In a randomized crossover study (n = 18), subjects consumed no broccoli for 16 days or the same diet with 200 g of cooked broccoli daily for 15 days and 100 g of broccoli on day 16. On day 17, all subjects consumed 200 g of cooked broccoli. Plasma and urine were collected for 24 h and analyzed for glucosinolate metabolites by LC-MS. Results: There was no effect of diet alone or interaction of diet with BMI. However, absorption doubled in HiBMI subjects (AUC 219%, plasma mass of metabolites 202% compared to values for LoBMI subjects) and time to peak plasma metabolite values and 24-h urinary metabolite also increased, to 127% and 177% of LoBMI values, respectively. Conclusion: BMI impacts absorption and metabolism of glucosinolates from cooked broccoli, and this association must be further elucidated for more efficacious dietary recommendations. Clinical Trial Registration: This trial was registered at clinicaltrials.gov (NCT03013465).